Longer door-to-balloon times predict poorer outcomes following primary angioplasty. (22nd September 2015) - Hetherington, SL; Adam, Z; Myagerimath, S; Twomey, D; Morley, R; Carter, J; Muir, DF; Hall, JA; Wright, RA; Swanson, N; Sutton, AGC; de Belder, MA
Abstract : Background: Minimising delays in time to reperfusion remains a priority with the evolution of primary percutaneous coronary intervention (PPCI) as the gold standard therapy for ST-segment elevation myocardial infarction (STEMI). Door-to-balloon (DTB) times of greater than 120 minutes have been associated with poorer outcomes following PPCI, and 90 minutes is the accepted target for optimal care. We analysed the effect of DTB time on mortality and major adverse cardiac and cardiovascular event (MACCE) rates in our PPCI registry. Methods: Retrospective analysis of prospectively collected data on 1208 patients presenting with STEMI and treated by PPCI, between February 2004 and November 2008 was performed. Clinical, procedural and outcome data were compared. Logistic regression and Cox proportional hazards models were used to estimate inhospital mortality and MACCE and mortality at 3 years, before and after adjustment for other important covariates. Results: A DTB time of less than 90 minutes was achieved in 859 cases (71%). Median DTB time was 44 minutes (interquartile range (IQR) 30–62 minutes) in the less than 90 minutes group and 122 minutes (IQR 104–151 minutes) in the over 90 minutes group. The baseline patient characteristics are shown in the table. Significant differences were observed between the groups in intra-aortic balloon pump (IABP) use and a history of peripheral vascular disease. Inhospital MACCE and mortality were significantly lower in the shorter DTB time group. After adjustment for other covariates (age, gender, history of diabetes, peripheral vascular disease, previous myocardial infarction, percutaneous coronary intervention or coronary artery bypass grafting, serum creatinine concentration, IABP use, preprocedure cardiogenic shock, three-vessel coronary artery disease) the DTB time continued to predict inhospital mortality (odds ratio (OR) 2.14, 95% CI 1.03 to 4.47, p = 0.042), but not MACCE (OR 1.67, 95% CI 0.94 to 2.97, p = 0.082). The effect on survival persisted at 3 years (fig; mortality <90 minutes 7.8% vs >90 minutes 14.0%; hazard ratio 1.81, p = 0.003). After adjustment, 3-year mortality remained significantly lower in the less than 90 minute DTB time group (hazard ratio 1.97, 95% CI 1.31 to 2.97, p = 0.001). Conclusions: The majority of patients treated with PPCI at our institution achieve DTB times of less than 90 minutes. Shorter DTB times are associated with a halving of inhospital mortality and a 6.2% absolute reduction in mortality at 3 years. Reducing DTB times should therefore remain a high priority when establishing a PPCI service and should be subject to regular audit.